Evaluation of self-regulated learning on problem-solving skills in online basic Physics learning during the COVID-19 pandemic - Ahmad Abtokhi; Budi Jatmiko; Wasis Wasis (OmniaScience, 2021)
The problems of learning physics have experienced increasingly complex obstacles amid the demands of online learning due to the COVID-19 pandemic. The purpose of this study is to explain the basic physics learning process through an online system during a pandemic, by evaluating the Self-Regulated Learning (SRL) approach to Problem-solving Skills (PSS). Data were collected through distributing questionnaires, interviews and documentation studies, then analyzed. This study shows that the applied SRL has been implemented well, but has not been optimal in improving PSS in online Basic Physics learning. The unpreparedness of technological devices and the competence of educators and students become obstacles that result in difficulties in solving physics problems so that the expected results are not following the expected learning targets. Also, this study shows the difficulty of learning physics online during the pandemic. Thus, a responsive physics learning model is needed with conditions that allow the delivery of physics material to be well understood, even though it is delivered through digital media. This is a demand that needs the attention of all parties so that the achievement of online learning targets remains optimal and effective in increasing the problem-solving skills of students during the COVID-19 pandemic.